A compendium of low vision learning activities from around the world. - Dalton, Helen (ed); Junghans, Barbara (ed) (Australian Learning and Teaching Council (ALTC), 2011)
This compendium is the culmination of a low vision course benchmarking process that involved 19 colleges or schools of optometry across Australasia, North America and the United Kingdom. As a thank you for taking the time to help with the benchmarking process, participating educators were asked to contribute one favourite or popular learning activity for inclusion in the compendium and thus provide a useful resource for each other. Fourteen educators submitted activities that they knew from experience would have significant impact on the student. These activities have been arranged in a continuum, from those requiring no previous knowledge to those demanding full understanding of many aspects of caring for the low vision patient. The compendium was produced as part of the 'Delivering optometric graduates ready for practice beyond the cities and ready to service an ageing population' project.